Cladophora spp. Extracts Show Remarkable Antibacterial Potential Against Pseudomonas aeruginosa: Ekstrak Cladophora spp. Menunjukkan Potensi Antibakteri yang Luar Biasa Terhadap Pseudomonas aeruginosa - Hussain, Hussain Adnan; Mezal, Ezat H.; Alashoor, Ahmed. S. (Academia Open, 2024)
Background: Bacterial resistance, influenced by genetic processes and adaptive strategies, necessitates the discovery of novel antibacterial agents, especially from natural sources. Specific Background: Pseudomonas aeruginosa, a notorious pathogen in urinary tract infections (UTIs), demonstrates considerable resistance to conventional therapies, necessitating alternative therapeutic approaches. Knowledge Gap: Research indicates that while natural sources like Cladophora spp. offer antibacterial agents, their effectiveness in combating P. aeruginosa resistant strains remains underexplored. Aims: This study aims to evaluate the antibacterial potential of Cladophora spp. algae extracts against Pseudomonas aeruginosa isolated from UTIs, utilizing solvent extraction, MIC determination, disc diffusion assays, and GC-MS analysis to identify bioactive compounds. Results: All extracts, including those prepared with water, ethanol, and hexane, demonstrated inhibitory effects on P. aeruginosa. The hexane extract exhibited the most significant activity, with a mean zone of inhibition of 13.0 ± 0.7 mm at a concentration of 50%. GC-MS analysis identified several bioactive compounds potentially responsible for these effects. Novelty: This study is among the first to investigate Cladophora spp. as a source of antibacterial agents specifically targeting P. aeruginosa, providing new insights into the potential of algae-based therapeutics. Implications: Cladophora spp. holds promise as a source of novel antibacterial compounds, with potential for multidrug-resistant infections treatments. Further research is needed for clinical application. Highlights: Hexane Extract: Most effective against Pseudomonas aeruginosa. Novel Source: Cladophora spp. shows potential as antibacterial agent. GC-MS Findings: Identified key bioactive compounds. Keywords: Cladophora spp., Pseudomonas aeruginosa, antibacterial agents, natural extracts, GC-MS analysis